Intranasal application of a bifunctional pertactin-RTX fusion antigen elicits protection of mouse airway mucosa against Bordetella pertussis colonization - Carlos Espinosa-Vinals; Jana Holubova; Ondrej Stanek; Radim Osicka; Jiri Masin; Fresia Esther Arellano Herencia; Peter Sebo (mSphere)
ABSTRACT The adenylate cyclase toxin (ACT, AC-Hly, or CyaA) plays a key role in airway infections by Bordetella pertussis and ablates the oxidative burst and opsonophagocytic capacity of sentinel phagocytes. CyaA fragments eliciting toxin-neutralizing antibodies are considered prime antigen candidates for improved acellular pertussis (aP) vaccines but their contribution to aP-mediated protection against B. pertussis infection awaits demonstration. We explored whether hybrid antigens inducing simultaneously CyaA-neutralizing and anti-Prn opsonizing antibody responses can enhance aP-elicited protection of mouse airways from infection. Fusion to the N-terminus of an RTX908 antigen derived from CyaA enabled an accelerated folding of the pertactin passenger domain (rPrn) in function of calcium loading of the RTX908 moiety and conferred on the rPrn-RTX908 fusion antigen a superior capacity to induce functional anti-Prn IgG antibodies. The rPrn-RTX908 fusion antigen also elicited CyaA neutralizing anti-RTX antibodies that relieved the toxin-imposed inhibition of oxidative burst and opsonophagocytic uptake of B. pertussis bacteria by HL-60 cells exposed to physiological concentrations of the CyaA toxin. Intranasal immunization of mice with the rPrn-RTX908 antigen admixed into a PT and FHA-based aP vaccine elicited specific sIgA responses in mucosal secretions (saliva) and conferred a significantly enhanced protection of mouse lung and nose mucosa against B. pertussis infection, yielding a significantly accelerated clearance of bacteria from the infected lungs within a single day from infection. These results demonstrate the added value of anti-CyaA antibodies elicited by intranasal application of the rPrn-RTX908 fusion antigen in the protection of the airway against B. pertussis infection.IMPORTANCEDespite high vaccine coverage, unexpectedly massive whooping cough outbreaks are currently resurging in the most developed countries using the acellular pertussis (aP) vaccine. Accelerated development of improved aP vaccines, conferring a more complete and longer-lasting protection of the airway from Bordetella pertussis infection, is sorely needed. The highly immunosuppressive RTX adenylate cyclase toxin (CyaA) was proposed as a prime antigen candidate for inclusion into improved aP vaccines. We show here that a soluble RTX-derived antigen fused to the major opsonizing antibody target pertactin (rPrn-RTX908 hybrid) elicits opsonizing and toxin-neutralizing antibody responses that relieve the CyaA-imposed block of bactericidal opsonophagocytic uptake capacities of sentinel phagocytes. Intranasal immunization with the rPrn-RTX908 hybrid antigen then enables a significantly accelerated clearance of B. pertussis bacteria from mouse lungs and superior protection of mouse nasal mucosa from bacterial infection. These results unravel the added value of RTX antigen inclusion into the next generation of aP vaccines.